Efficient Scheduling for Machining Processes Considering Machine Unavailability Constraints - Liao, Lu-Wen; Chen, Yen-Chia (International Journal of Industrial Engineering: Theory, Applications and Practice, 2026)
This paper presents an integrated scheduling framework for single-machine machining processes to deal with the challenges posed by machine availability constraints due to preventive maintenance, cooling intervals, and unexpected breakdowns. Our primary objective was to minimize the makespan while accounting for job-specific processing and release times. The NP-hard nature of the problem rendered our initial mixed-integer programming model computationally prohibitive for large instances. Thus, we tailored a branch-and-bound algorithm to derive optimal solutions for small to medium-sized problems by leveraging specific upper and lower bounds. We then employed a genetic algorithm using a permutation-based chromosome and problem-specific decoder to generate near-optimal solutions for large-scale instances. This hybrid approach balances solution quality with computational efficiency, rendering it highly suitable for a wide range of practical industrial manufacturing applications.